North East India medicinal plants database (NEI-MPDB). (October 2022) - Kiewhuo, Kikrusenuo; Gogoi, Dipshikha; Mahanta, Hridoy Jyoti; Rawal, Ravindra K.; Das, Debabrata; Sastry, G. Narahari
Abstract: The rich biodiversity of North East India is one of the recognized biodiversity hotspots of the world. This region comprises of eight states (Assam, Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim, and Tripura) with diverse ethnic communities having invaluable traditional knowledge/practices, passed through genesis. The medicinal plants in this region are rich in natural products/phytochemicals and have been used extensively by pharmaceutical industries. The present study is an attempt to develop a comprehensive resource of the medicinal plants with a quantitative analysis of the phytochemicals which can enhance knowledge on therapeutic indications and contribute in drug discovery and development. The database is a collection of 561 unique plants comprising of 9225 phytochemicals. The physiochemical properties of the phytochemicals were analyzed using indigenous python scripts whereas for the ADMET properties, open access servers were used. The data available in NEI-MPDB will help to connect the cutting-edge approach of various research groups and will help to translate the information into economic wealth by the pharmaceutical industries. The database is openly accessible at https://neist.res.in/neimpdb/ . Graphical Abstract: Development of a database of medicinal plants and traditional practices among the ethnic communities of North East India. ga1 Highlights: A database of medicinal plants integrating different ethnic communities of North East India was developed. Repository of taxonomy, ethnobotany, phytochemicals, and ADMET properties of medicinal plants. The extensive phytochemical data helping traditional drug discovery. A robust knowledge base for the conservation of ethnobotanical and bio-resources of NE region of India.